Compare Between Gait Analysis of Patient with Ilizarov Leg and Prosthesis Leg - Jawad, Omyia Mahmoud; Abass, Sadiq Jaffar; Dia’a, Safa Kadiam (Al-Nahrain Journal for Engineering Sciences, 2020)
Gait analysis can be described as a field of biomechanical engineering dealing with the subject of human locomotion. This study aimed to identify the effect of Ilizarov on gait when the presence the above-knee prosthesis. The study was made on a 50-year-old male patient was underwent correction right tibia with Ilizarov fixation due to war accident in July 2012. Also, this accident led to trans-femoral amputation. Two-dimensional gait system of a synchronized 25 Hz camera with an AMTI force platform was use for measuring gait kinematics and kinetics data while walking at a self-selected speed. These data can be used as standard measures in pathology studies, as input to theoretical joint models, and as input to mechanical joint simulators treated with Ilizarov and prosthetics.